Arbuscular mycorrhizal fungi improve the disease resistance of Lycium barbarum to root rot by activating phenylpropane metabolism - Li, Nan; Chen, Wei; Wang, Bin; Zhang, Chongqing; Wang, Yupeng; Li, Ruiyun; Yan, Yuke; He, Jing (Frontiers in Plant Science, 2024)
Root rot is one of the common diseases of Lycium barbarum. Pathogens can cause devastating disasters to plants after infecting host plants. This study investigated the effect of arbuscular mycorrhizal fungi (AMF) Rhizophagus intraradices inoculation on phenylpropane metabolism in L. barbarum and evaluated its resistance to root rot. The experiment was set up with AMF inoculation treatments (inoculated or not) and root rot pathogen-Fusarium solani inoculation treatments (inoculated or not).The results showed that AMF was able to form a symbiosis with the root system of L. barbarum, thereby promoting plant growth significantly and increasing plants' resistance to disease stress. The plant height of AMF-colonized L. barbarum increased by 24.83% compared to non-inoculated diseased plants. After inoculation with AMF, the plant defense response induced by pathogen infection was stronger.When the enzyme activity of the leaves reached the maximum after the onset of mycorrhizal L. barbarum, phenylalanine ammonia-lyase, cinnamic acid-4-hydroxylase, and 4-coumaric acid-CoA ligase increased by 3.67%, 31.47%, and 13.61%, respectively, compared with the non-inoculated diseased plants. The products related to the lignin pathway and flavonoid pathway downstream of phenylpropane metabolism such as lignin and flavonoids were also significantly increased by 141.65% and 44.61% compared to nonmycorrhizal diseased plants. The activities of chitinase and β-1,3-glucanase increased by 36.00% and 57.96%, respectively. The contents of salicylic acid and jasmonic acid were also 17.7% and 31.63% higher than those of nonmycorrhizal plants in the early stage of plant growth, respectively. The results indicated that AMF significantly promoted plant growth and enhanced disease resistance by increasing enzyme activities and the production of lignin and flavonoids.字体: (默认)Times New Roman, 小四 设置格式[李南]:Afterwards we isolated and screened the spores using wet sieve decantation-sucrose centrifugation, stained them (Kumar et al., 2008), and observed and counted them under a somatic microscope to finally determine the number of viable spores present in the inoculum.